Characterization of Bacillus subtilis GA2(1) mannanase expressed in Escherichia coli Rosetta (DE3) for enzymatic production of manno-oligosaccharides from spent coffee grounds and in vitro assessment of their prebiotic properties - Pariyapat Puengsawad; Chanitchote Piyapittayanun; Thornthan Sawangwan; Sudathip Chantorn (Agriculture and Natural Resources, 2021)
In modern times, prebiotics have received increasing, widespread interest as a functional food, with growing demand in the global functional food market. Most commercial prebiotics are non-digestible oligosaccharides. Recombinant mannanase was characterized and investigated for its potential in prebiotic production. The recombinant mannanase from Bacillus subtilis GA2(1) had maximal activity at pH 7.0 and 50°C, and was highly activated by Co2+ while strongly inhibited by Hg2+. This enzyme effectively hydrolyzed pretreated spent coffee grounds (SCG) with final manno-oligosaccharides (MOS) products, mainly mannobiose (M2) and mannotriose (M3). Two types of lyophilized (LP) and non-lyophilized (NP) hydrolysate products had total hydrolysis levels of 25.2% and 28.2%, respectively. The de Man, Rogosa and Sharpe (MRS) broth supplemented with either LP or NP significantly (p < 0.05) increased the growth of the tested probiotic strains. Nutrient broth supplemented with either LP or NP strongly inhibited the growth of the tested pathogen strains. Interestingly, Lb. plantarum TISTR 1465 cultured in MRS-NP medium had a higher %hydrophobicity than that in the commercial prebiotic. This study developed an alternative and eco-friendly process to produce high-quality prebiotics and indicated the potential to add value to SCG as a major industrial waste.